Visualisasi Efek Perubahan Fungsi Lahan Menggunakan Maksimum Spanning Tree dengan Pembobot Korelasi - Dwi Risky Arifanti (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
This study aims to visualize the effect of land use change using Maximum Spanning Tree with correlation weight between variables. In addition to know the most dominant factors affect the dependent variable. Based on data of land conversion of regency in South Sulawesi on year 2014, it is found that the percentage of villages experiencing the change of non-sawah land into rice field is the dominant factor. The percentage of districts / municipalities that have villages experiencing non-sawah land conversion to rice fields of 16.77 is expected to be reduced to 8.33%.